Controlling the Diameter of Single-Walled Carbon Nanotubes by Improving the Dispersion of the Uniform Catalyst Nanoparticles on Substrate - Chen, Junjun; Xu, Xiangju; Zhang, Lijie; Huang, Shaoming (Nano-Micro Letters, 2015)
To have uniform nanoparticles individually dispersed on substrate before single-walled carbon nanotubes (SWNTs) growth at high temperature is the key for controlling the diameter of the SWNTs. In this letter, a facile approach to control the diameter and distribution of the SWNTs by improving the dispersion of the uniform Fe/Mo nanoparticles on silicon wafers with silica layer chemically modified by 1,1,1,3,3,3-hexamethyldisilazane under different conditions is reported. It is found that the dispersion of the catalyst nanoparticles on Si wafer surface can be improved greatly from hydrophilic to hydrophobic, and the diameter and distribution of the SWNTs depend strongly on the dispersion of the catalyst on the substrate surface. Well dispersion of the catalyst results in relatively smaller diameter and narrower distribution of the SWNTs due to the decrease of aggregation and enhancement of dispersion of the catalyst nanoparticles before growth. It is also found that the diameter of the superlong aligned SWNTs is smaller with more narrow distribution than that of random nanotubes.